2021
DOI: 10.1186/s12885-021-08745-0
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of a combination of single nucleotide polymorphisms and clinical parameters to predict clinically relevant toxicity associated with fluoropyrimidine and platinum-based chemotherapy in gastric cancer

Abstract: Background Fluoropyrimidine plus platinum chemotherapy remains the standard first line treatment for gastric cancer (GC). Guidelines exist for the clinical interpretation of four DPYD genotypes related to severe fluoropyrimidine toxicity within European populations. However, the frequency of these single nucleotide polymorphisms (SNPs) in the Latin American population is low (< 0.7%). No guidelines have been development for platinum. Herein, we present association between clinical factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…This review included five studies that reported contradictory results regarding the association of various SNPs in the DPYD gene with capecitabine toxicity [ 21 , 23 , 25 , 26 , 28 , 31 ]. These results agree with studies conducted in patients with other cancers or treated with other FPs [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. A meta-analysis of six studies in 6119 European ancestry (international) patients with solid neoplasms (gastrointestinal, breast, pancreas, bile duct, among others) treated with FPs reported that the DPYD rs1801160 SNP was associated with an increased risk of toxicity, indicating that this SNP should be included in clinical practice [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This review included five studies that reported contradictory results regarding the association of various SNPs in the DPYD gene with capecitabine toxicity [ 21 , 23 , 25 , 26 , 28 , 31 ]. These results agree with studies conducted in patients with other cancers or treated with other FPs [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. A meta-analysis of six studies in 6119 European ancestry (international) patients with solid neoplasms (gastrointestinal, breast, pancreas, bile duct, among others) treated with FPs reported that the DPYD rs1801160 SNP was associated with an increased risk of toxicity, indicating that this SNP should be included in clinical practice [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study found a significant association between the DPYD rs1801160 and rs2297595 SNPs and severe adverse events during therapy [ 47 ]. Two recent studies in patients with gastrointestinal neoplasms ( n = 80 and 93), of Jordanian (Jordan) and Latin American (Chile) origin, reported a significant association between the DPYD rs1801265 SNP and adverse events during FP therapy [ 49 , 50 ]. However, two other studies conducted in patients with gastrointestinal neoplasms ( n = 503 and 113), of European and African American origin (Croatia, USA), found no significant association between this SNP and FP severe toxicity [ 46 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review also shows that few novel variants in the DPYD gene have been reported in Middle Eastern 81 populations with a paucity of data in Latin American populations 78 , highlighting the need for more studies in these populations. Indeed, further studies are needed in all populations (European and non-European) to fully understand the spectrum of harmful mutations which occur in this gene.…”
Section: Discussionmentioning
confidence: 79%
“…Only 1 cohort study from Chile was identified in the Latin American population 78 and the authors examined 3 missense DPYD polymorphisms considered to have normal DPD enzyme function by the CPIC guideline, c.85T>C, c.496A>G and c.1627A>G (Supplementary Table 5, Supplementary Results).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the most reliable SNP markers of fluoropyrimidine toxicity are DPYD*2A (rs3918290), DPYD-c.2846 A>T (rs67376798), DPYD-Hap-B3 (rs56038477) and DPYD*13 (rs55886062). 9 The "rs" prefix (e.g., rs3918290) in the SNP designation (SNP accession number) is an acronym for RefSNP (rs).…”
Section: Generation Of New Dna Sequence Variants and Their Relevance ...mentioning
confidence: 99%